Global trends and characteristics of ecological security research in the early 21st century: A literature review and bibliometric analysis. (April 2022) - Liu, Chenli; Li, Wenlong; Xu, Jing; Zhou, Huakun; Li, Changhui; Wang, Wenying
Graphical abstract: Highlights: The evolution of hot topics on ecological security research was visually analyzed. Ecological security research is at its rapid growth stage of development. China is the most active country in ecological security research. The focal topics have switched from ecological security assessment to ecological security pattern construction. Abstract: With the worsening of global and local environmental problems, ecological security has a vital role to play in sustainable development, and has become a worldwide topic of concern in the 21st century. This study used bibliometric analysis to comprehensively review the progress of global research in ecological security from 2000 to 2020 to provide an overview for future directions. We analyzed 761 publications related to ecological security from this period, covering 34 countries, 370 journals, 631 institutions, 585 funding agencies, and 2680 authors. The results showed that the majority of publications (71.75%) appeared from 2014 to 2020, with research conducted mostly in China, followed by the USA and Russia. The top 10 active institutions were all Chinese; the Chinese Academy of Sciences was the most productive institution, and also had the highest number of citations. China was at the center of the international cooperation network, with the highest collaboration with the USA, Australia, and Canada. Funding from the National Natural Science Foundation of China (NSFC) has supported the highest number of publications. The top two productive journals in this area were Sustainability and Ecological Indicators . Keyword co-occurrence and frequency analysis showed that "ecological security patterns, " "ecosystem services, " "ecological security assessment, " "sustainable development, " and "land use change" were the main topics, whereas "GIS, " "PSR model, " "ecological footprint, " "remote sensing, " "MCR model, " and "DPSIR model" were the most commonly used research technologies and models. Our findings showed that the focal topics have switched from ecological security assessment to ecological security patterns. We believe that these results would contribute to practitioners' and researchers' better understanding of worldwide ecological security research and facilitate future investigations.